Analisis Kondisi Pembelajaran Bahasa Di Sekolah Dasar - Kuntarto, Eko; Soleh, Muhammad; Sayyidatunnisa, Zhafira; Humaila, Annisa; Ramdahani, Occha Kayla (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the condition of language learning in SDN 187/I Teratai. The method used in this study is a qualitative approach with a case study design. Data was collected through interviews, observations, and analysis of documents involving teachers, students, and parents. The results of the study show that the teaching methods applied are still traditional, with limited learning resources. In addition, the support of parents and the school environment for language learning is also minimal. Therefore, it is necessary to develop more interactive teaching methods and increase access to varied learning resources. The existence of these steps is expected to significantly improve the language skills of students at SDN 187/I Teratai, so that they are better prepared to face challenges in the future.